An exploratory trial exploring the use of a multiple intelligences teaching approach (MITA) for teaching clinical skills to first year undergraduate nursing students. (December 2015) - Sheahan, Linda; While, Alison; Bloomfield, Jacqueline
Summary: Background: The teaching and learning of clinical skills is a key component of nurse education programmes. The clinical competency of pre-registration nursing students has raised questions about the proficiency of teaching strategies for clinical skill acquisition within pre-registration education. Objectives: This study aimed to test the effectiveness of teaching clinical skills using a multiple intelligences teaching approach (MITA) compared with the conventional teaching approach. Design: A randomised controlled trial was conducted. Participants were randomly allocated to an experimental group (MITA intervention) (n = 46) and a control group (conventional teaching) (n = 44) to learn clinical skills. Setting: Setting was in one Irish third-level educational institution. Participants: Participants were all first year nursing students (n = 90) in one institution. Methods: The experimental group was taught using MITA delivered by the researcher while the control group was taught by a team of six experienced lecturers. Participant preference for learning was measured by the Index of Learning Styles (ILS). Participants' multiple intelligence (MI) preferences were measured with a multiple intelligences development assessment scale (MIDAS). All participants were assessed using the same objective structured clinical examination (OSCE) at the end of semester one and semester two. MI assessment preferences were measured by a multiple intelligences assessment preferences questionnaire. The MITA intervention was evaluated using a questionnaire. Results: The strongest preference on ILS for both groups was the sensing style. The highest MI was interpersonal intelligence. Participants in the experimental group had higher scores in all three OSCEs (p < 0.05) at Time 1, suggesting that MITA had a positive effect on clinical skill acquisition. Most participants favoured practical examinations, followed by multiple choice questions as methods of assessment. MITA was evaluated positively. Conclusion: The study findings support the use of MITA for clinical skills teaching and advance the understanding of how MI teaching approaches may be used in nursing education. Highlights: MITA can help nursing students to learn using their different intellectual strengths or abilities. Identifying learning and assessment preferences early is important if students are to understand how they learn best. In this exploratory trial MITA created a positive and motivating environment for learning because it is student focused.